Pertanggungjawaban Administratif Juru Parkir di Tepi Jalan Umum Dalam Pemungutan Retribusi - Hasfar Fuadi; Ilyas Ismail; Muhammad Saleh (Media Iuris, 2021)
AbstractThis paper uses a juridical empirical research method. Juridical research is using a statutory approach, namely Qanun/Perda (das sollen), while empirical research uses a field approach (das sein) by conducting direct interviews with parking attendants and parking retribution users. This study aims to understand and determine the responsibility of parking attendants on the edge of public roads in collecting retribution and applying sanctions to irresponsible parking attendants on the edge of public roads. The results of the study show that the parking attendant is required to use the official clothes/vest provided by the Banda Aceh City Transportation Service, the parking attendant at the time of collecting the parking fee is required to submit a coupon to the user of the retribution service as proof of the parking levy collection and the parking attendant is obliged to submit the levy result to the Banda City Government Aceh through the Quotation Officer assigned in accordance with the provisions that have been set, but if the parking attendant does not carry out his obligations, he will be given a sanction in the form of cancellation of the Management Agreement for the Collection of Parking Retribution. By submitting the coupon as proof of payment of the parking fee, the user of the levy service will count the number of vehicles entering and leaving. Keywords: Accountability; Retribution; Parking.AbstrakTulisan ini menggunakan metode penelitian yang bersifat yuridis empiris. Penelitian yuridis adalah menggunakan pendekatan peraturan perundang-undangan yaitu Qanun/Perda (das sollen), sedangkan penelitian empiris menggunakan pendekatan lapangan (das sein) dengan melakukan wawancara langsung terhadap Juru Parkir dan pengguna retribusi parkir. Penelitian ini bertujuan untuk memahami dan mengetahui pertanggungjawaban Juru Parkir di tepi jalan umum dalam pemungutan retribusi dan penerapan sanksi terhadap Juru Parkir di tepi jalan umum yang tidak bertanggung jawab. Hasil penelitian bahwa Juru Parkir wajib menggunakan pakaian/rompi resmi yang diberikan oleh Dinas Perhubungan Kota Banda Aceh, Juru Parkir pada saat memungut retribusi parkir wajib menyerahkan kupon kepada pengguna jasa retribusi sebagai bukti pungutan retribusi parkir dan Juru Parkir wajib menyerahkan hasil retribusi kepada Pemerintah Kota Banda Aceh melalui Juru Kutip yang ditugaskan sesuai dengan ketentuan yang telah ditetapkan, namum apabila Juru Parkir tidak melaksanakan kewajibannya maka akan diberikan sanksi berupa pembatalan Surat Perjanjian Tata Kelola Pemungutan Retribusi Parkir. Dengan diserahkannya kupon sebagai tanda bukti pembayaran retribusi parkir maka pengguna jasa retribusi akan terhitung jumlah kendaraan yang masuk dan keluar.Kata Kunci: Pertanggungjawaban; Retribusi; Parkir.